2007
DOI: 10.1111/j.1445-2197.2006.03993.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Pulmonary Complications in Upper Abdominal Surgery

Abstract: We recommend a detailed pulmonary examination and spirometry in patients who will undergo UAS by chest physicians to identify the patients at high risk for POPC, to manage respiratory problems of the patients before surgery and also to help surgeons to take early measures in such patients before a most likely POPC occurrence. Improvement of lung function in those patients at risk for POPC before operation may decrease morbidity in surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
31
4
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 43 publications
(89 reference statements)
14
31
4
4
Order By: Relevance
“…Accordingly, in this study postoperative pneumonia was the most common postoperative pulmonary complication (85.2%). This is consistent with study conducted by Kanat et al [24], Gerard et al [27] and Brooks [26] where pneumonia was the leading postoperative pulmonary complication in their study. But it was higher comparable to study conducted by Toori et al, Modell et al and Medeiros [21][22][23] which was 16%, 45% and 37.2% respectively.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Accordingly, in this study postoperative pneumonia was the most common postoperative pulmonary complication (85.2%). This is consistent with study conducted by Kanat et al [24], Gerard et al [27] and Brooks [26] where pneumonia was the leading postoperative pulmonary complication in their study. But it was higher comparable to study conducted by Toori et al, Modell et al and Medeiros [21][22][23] which was 16%, 45% and 37.2% respectively.…”
Section: Discussionsupporting
confidence: 83%
“…This rate is higher than the reported rates by Toori et al and Finlay et al [20,21] which was 8% and 5% respectively. However, compared to Medeiros et al, Fisher et al and Kanat et al [22][23][24] (PPC rates of 33.9%, 37% and 58.3% respectively), our reported rate of PPC was quite less. The above mentioned statistics clearly depict a wide range of PPC incidence because of difference in patient population and criteria used to define the PPC in different populations [9,25].…”
Section: Discussioncontrasting
confidence: 49%
“…79,80,89 The risk of postoperative complications also depends on the type of surgery. The rate of complication is higher in patients undergoing abdominal surgery [90][91][92] and is also increased with aortic aneurysm repair, [93][94][95][96] vascular, 74,78,79,93 thoracic, 83,90,93,96 and neck surgery. 83,96,97 Gupta et al have shown an increased risk of postoperative complications (39% vs 18%), higher rate of transfer to ICU (24% vs 9%), and increased length of hospital stay in patients with obstructive sleep apnea compared with control subjects matched for age, sex, and body mass index (BMI).…”
Section: Evidence On Sleep Apnea As a Risk Factor For Perioperative Cmentioning
confidence: 99%
“…Furthermore, patients with altered levels of consciousness, neurological disorders, history of pulmonary disease, older age and gastroesophageal reflux disease are at risk of aspiration pneumonia [4,5]. The 30° elevation of the upper body has been shown to reduce the risk of aspiration pneumonia in the intensive care unit (ICU) [6].…”
Section: Introductionmentioning
confidence: 99%